Imperforated anus. Clinical-epidemiologic approach - Baeza Herrera Carlos; Rodríguez Calderón Roberto Lucas; Villalobos Catillejos Alin (Instituto Nacional de Pediatría, 2014)
Introduction. Ano-rectal malformations are among the most common defects in clinical practice. Unfortunately we do not know how many new cases occur each year in our country. The aim of this study is to show a clinical-epidemiological aspect of the problem. Material and methods. It is a retrospective study over a period of three years in which we studied 72 charts. We analyzed universal variables such as sex, age, prenatal control, birth weight etc. There were 42 (58.3%) males, and 30 females (41.8%). Their age ranged from one to eight days, the mean birth weight was 2,827 grams, the average age of parents was 23.4 and 25.3 years. Results. Fourty two (58.3%) patients required colostomy; only 17 had an associated malformation. There were three deaths. Conclusions. Anorectal malformations are severe and common defects. We propose that a national registry should be mandatory.